ANALISIS IMPLEMENTASI KEBIJAKAN PEMBERDAYAAN UMKM DI KABUPATEN KLATEN “Studi pengecoran logam di Kecamatan Ceper” - Sulistyo Ady Purnomo; Achmad Taufiq; Suwanto Adhi (Journal of Politic and Government Studies, 2014)
AbstractIn an era of global competition is increasingly fierce and open aphenomenon that must be faced by businesses to produce products that have astrong competitiveness and competitive price products. MSMEs as one of thesupporting force of the movement of domestic trade and driving economicdevelopment has a very important role and is crucial in order to improveregional and national economies, So to encourage the presence of these UMKMneed a policy that supports UMKM in order to develop, and can help economicgrowth. As Klaten district in empowering the UMKM sector, metal cast intoone of the local revenue contributor.This study used a qualitative method is to conduct a survey andinterviews with the cast metal yng businesses located in the village of Batursubdistrict Ceper Klaten to obtain data on the role of government in enablingbusinesses of cast metal which decreased.The results showed that of the answer businessmen about government'srole in the Klaten district policy UMKM sector, especially in the village ofBatur cast metal Ceper District of Klaten District overall has been going well,but there are some indicators which businesses are still not good and not inaccordance expectations. From the results of this study appear several solutionsto improve local government services to entrepreneurs Klaten cast metal. Toimprove the success rate of these policies certainly Klaten District Government,Cooperative Batur victorious and the business must work in synergy.